Penguatan karakter moderasi beragama melalui literasi keagamaan dalam pendidikan kristiani - Fransiskus Sawan; Marselus Ruben Payong (KURIOS, 2023)
Religious moderation is one of the themes that has been frequently researched in recent years. This topic is examined from various perspectives, including a Christian perspective. In the context of Christian education, studies on this topic generally focus on efforts to build a biblical foundation for moderate religious perspectives, attitudes, and practices. These studies are essential as a form of religious literacy. But so far, there has yet to be research on strengthening the character of religious moderation through the religious literacy movement in Christian education so that the values of religious moderation are internalized into the nature of students. This research aims to fill this gap. The method used is a descriptive qualitative method with a literature study approach. The results show that strengthening the character of religious moderation will be effective if religious literacy is carried out as a participatory movement through learning activities, developing school culture, extracurricular activities, and activities at home/church/community. The results of this study enrich the literature on moderation and religious literacy. They are helpful as an essential input for educators committed to forming the character of religious moderation in students.Â AbstrakModerasi beragama merupakan salah satu tema yang sering diteliti selama beberapa tahun terakhir ini. Topik ini dikaji dari berbagai cara pandang termasuk cara pandang kristiani. Dalam konteks pendidikan kristiani, studi tentang topik ini umumnya berfokus pada upaya membangun landasan biblis cara pandang, sikap dan praktik hidup beragama yang moderat. Berbagai kajian ini penting sebagai bentuk literasi agama. Namun sejauh ini, belum ada penelitian tentang model penguatan karakter moderasi beragama melalui gerakan literasi agama dalam pendidikan kristiani agar nilai-nilai moderasi beragama terinternalisasi menjadi karakter peserta didik. Penelitian ini bertujuan mengisi gap ini. Metode yang digunakan adalah metode kualitatif deskriptif dengan pendekatan studi kepustakaan. Hasilnya menunjukkan bahwa penguatan karakter moderasi beragama akan efektif jika literasi keagamaan dilakukan sebagai gerakan partisipatif melalui kegiatan pembelajaran, pengembangan budaya sekolah, kegiatan ekstrakurikuler dan kegiatan di rumah/gereja/masyarakat. Hasil penelitian ini memperkaya literatur moderasi dan literasi keagamaan serta berguna sebagai input yang penting bagi para pendidik yang berkomitmen untuk membentuk karakter moderasi beragama dalam diri peserta didik.